Dermatological diseases in palliative care patients: a prospective study of 271 patients - Neloska, Lenche; Damevska, Katerina; Kuzmanova, Andjelka; Pavleska, Lidija; Kostov, Milenko; Petreska Zovic, Biljana (John Wiley & Sons Ltd., 2017)
Background: Numerous risk factors place palliative care patients at an increased risk of skin infections, dermatitis, and pressure sores. Furthermore, worsening of chronic skin disorders can be expected, as well as the development of treatment-induced and malignancy-related dermatoses. The objective of the present study was to investigate the prevalence and treatment of dermatological conditions in patients receiving hospital- based palliative care. Methods: Two hundred seventy-one palliative patients were enrolled. All assessments were conducted by dermatologists. Skin lesions were classified into seven categories: infections, skin tumors, dermatitis, chronic wounds, nail and hair disorders, pruritus, and other unclassified conditions. Treatment modalities were classified as topical only or systemic. Results: Overall, 1,267 dermatological conditions were recorded, 49 % of which were hospital-acquired. All patients had at least one dermatological condition, and more than 50 different dermatological disorders were noted. The most common group of skin disorders was dermatitis (18.3 % of all dermatological conditions), followed by nail and hair disorders (17.5 %). Almost 16 % of dermatological conditions were treated systemically. Conclusions: Dermatological conditions are a common and clinically significant problem for palliative patients. The inclusion of dermatologists in multidisciplinary palliative teams should prove helpful in the management of these patients.
Dermatologische Erkrankungen bei Palliativpatienten: eine prospektive Studie an 271 Patienten